Zn-0.8Mg-0.2Sr (wt.%) Absorbable Screws-An In-Vivo Biocompatibility and Degradation Pilot Study on a Rabbit Model - Klíma, Karel; Ulmann, Dan; Bartoš, Martin; Španko, Michal; Dušková, Jaroslava; Vrbová, Radka; Pinc, Jan; Kubásek, Jiří; Ulmannová, Tereza; Foltán, René; Brizman, Eitan; Drahoš, Milan; et al. (Materials (Basel, Switzerland), 2021)
In this pilot study, we investigated the biocompatibility and degradation rate of an extruded Zn-0.8Mg-0.2Sr (wt.%) alloy on a rabbit model. An alloy screw was implanted into one of the tibiae of New Zealand White rabbits. After 120 days, the animals were euthanized. Evaluation included clinical assessment, microCT, histological examination of implants, analyses of the adjacent bone, and assessment of zinc, magnesium, and strontium in vital organs (liver, kidneys, brain). The bone sections with the implanted screw were examined via scanning electron microscopy and energy dispersive spectroscopy (SEM-EDS). This method showed that the implant was covered by a thin layer of phosphate-based solid corrosion products with a thickness ranging between 4 and 5 µm. Only negligible changes of the implant volume and area were observed. The degradation was not connected with gas evolution. The screws were fibrointegrated, partially osseointegrated histologically. We observed no inflammatory reaction or bone resorption. Periosteal apposition and formation of new bone with a regular structure were frequently observed near the implant surface. The histological evaluation of the liver, kidneys, and brain showed no toxic changes. The levels of Zn, Mg, and Sr after 120 days in the liver, kidneys, and brain did not exceed the reference values for these elements. The alloy was safe, biocompatible, and well-tolerated.
Keywords: in-vivo biocompatibility; zinc; magnesium; systemic reactions; toxicity; alloy accumulation; internal organs; strontium; bioabsorbable metals; biocompatibility